2009
DOI: 10.1002/app.30493
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane networks from different soy‐based polyols by the ring opening of epoxidized soybean oil with methanol, glycol, and 1,2‐propanediol

Abstract: A series of polyols with a range of hydroxyl (OH) numbers based on soybean oil and epoxidized soybean oil were prepared by oxirane ring opening with methanol, glycol, and 1,2-propanediol. The polyols, with average functionalities varying from 2.6 to 4.9, were characterized. Novel cast polyurethane resins were synthesized from these polyols and 2,4-toluene diisocyanate. The sol fraction of the network decreased as the OH number of the polyol from which it was synthesized increased. None of the samples were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 31 publications
1
46
0
5
Order By: Relevance
“…It was found that the storage modulus at room temperature, the glass transition temperature, and the crosslink density of the epoxy blend decreased with increasing content of EVO, while fracture toughness and flexural modulus were increased with increasing amount of EVO [17][18][19]. The epoxide rings of EVO can be ring-opened by alcohols [20] or acids [21,22] to introduce other functionalities. After the epoxide rings had been opened, hydroxyl groups were introduced, and polyurethanes with a wide range of properties can be produced by the reactions between hydroxyl groups and diisocyanates [23].…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the storage modulus at room temperature, the glass transition temperature, and the crosslink density of the epoxy blend decreased with increasing content of EVO, while fracture toughness and flexural modulus were increased with increasing amount of EVO [17][18][19]. The epoxide rings of EVO can be ring-opened by alcohols [20] or acids [21,22] to introduce other functionalities. After the epoxide rings had been opened, hydroxyl groups were introduced, and polyurethanes with a wide range of properties can be produced by the reactions between hydroxyl groups and diisocyanates [23].…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand polymer material based on HDI is characterized by high elasticity, two times higher tensile strength and modulus of elasticity than polyurethane elastomer based on polyol from soybean oil and HDI, described in the literature [29]. At the same time it presents comparable hardness in the Shore's A scale (67.4-87.7 Sh°A) [30][31][32] to polyurethane elastomers based on different vegetable oils. Moreover, the analysis of mechanical tests indicate that, application of aromatic isocyanate, toluene-2,4-diisocyanate, results in obtaining the composition Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl (-OH) numbers of polyols were 168, 224, 248 mg KOH g -1 , respectively. The neat soy polyol-based polyurethane (PU) was prepared from three polyols with IPDI using previously reported methods [32], which preparation procedures are shown in Fig. 1.…”
Section: Synthesis Of Polyurethane Nanocompositesmentioning
confidence: 99%